Comparison Analysis Between Accuracy of CAPM and APT Models in Predicting Return of IDX-30 Stocks during Covid-19 Pandemic - Siji Jati Sindhuarta; Ricky Albert Husni; Tumpal Samosir (Universitas Mercu Buana, 2023)
This study is done to analyze and compare the accuracy of Capital Asset Pricing Model (CAPM) and Arbitrage Pricing Theory (APT) Model in predicting stocks’ actual return. The purpose of the study is to find the discrepancy of accuracy of CAPM and APT models in predicting company stocks’ return registered in IDX-30 index from Indonesian Stock Exchange from January 2020-2022. The period is chosen because of the Covid-19 pandemic in Indonesia. The chosen stocks are the stocks which have positive return, never leave the index, never have any changes in stocks’ amount in major and minor evaluation, never do stock split, and have routine dividend payout along the study’s period. The result is there is a significant difference between CAPM and APT models in predicting the actual return based on the result from t-test independent samples. Observed from the Mean Absolute Deviation (MAD) of the two models, CAPM model MAD is smaller than those from APT model, thus CAPM is the more accurate model in calculating return form IDX-30 stocks from January 2020-2022.